Mental Health dalam Perspektif Psikologi Positif Serta Korelasinya dalam Pendidikan Islam - Hadini Hadini; M. Imamuddin; Masbur Masbur; Mujiburrahman Mujiburrahman (Universitas Pahlawan Tuanku Tambusai, 2026)
The educational process requires good mental health in every student. Without it, it will be difficult to develop other potentials. Given that it is a prerequisite for successful educational implementation, it must be developed. One effort to develop mental health is through the role of Positive Psychology. This study employed a library research method. The researcher identified literature in the form of national and international journals, books, and research findings related to the topic under study, namely how Positive Psychology can improve a person's mental health. The literature review also explored various studies conducted by previous researchers. The results of this study revealed a perspective on psychology in improving human mental health. Based on the research findings, several points were made. First, mental health and Positive Psychology are strongly linked, with both striving to increase human happiness. Second, Positive Psychology plays a significant role in helping improve a person's mental health. Third, improving mental health through the role of Positive Psychology can increase the effectiveness of Islamic Religious Education (PAI) learning.